A Multisource Monitoring Data Coupling Analysis Method for Stress States of Oil Pipelines under Permafrost Thawing Settlement Load. (25th November 2020) - Jiang, Changliang; Chen, Pengchao; Li, Rui; Liu, Xiaoben
Abstract : Thaw settlement is one of the common geohazard threats for safe operation of buried pipelines crossing permafrost regions, as pipes need to bear additional bending stress induced by settlement load. In the presented study, a novel coupled data analysis method was proposed for stress state estimation of buried steel pipeline under thawing settlement load. Multisource data including pipe bending strain derived by inertial measurement unit, pipe longitudinal strain derived by strain gauges, and thawing displacement loads derived by soil temperature monitoring were used to estimate the pipe's mechanical states. Based on the derived data, finite element method-based pipe soil interaction model was established to predict pipe's actual stress distribution. A monitored pipe segment of one crude oil pipeline in northeast China operated since 2010 was adopted as a prototype for the investigation, monitoring data derived in the last ten years was employed to predict the settlement loading, and relative accurate stress results was obtained via the established pipe soil interaction model. The mean absolute error (MAE) of the predicted pipe stresses compared with the monitoring results in 2014, 2017, and 2018 are 5.77%, 12.13%, and 13.55%, respectively. Based on the analyzed stress results, it can be found that the investigated pipe was subjected to an increasing settlement load from 2010–2016, made the bending stress increased up to 149.5 MPa. While after 2016, due to the depth of frost soil in this area is no more than 3.5 m, the thawing settlement load almost remained constant after 2016. As the investigated pipe is made by X65 line pipe steel, the von-Mises stress in pipe is much smaller than the allowable one indicating pipe's structural safety status so far. The proposed method can also be referenced in the status monitoring of buried pipeline crossing other geological hazard regions.